Differential effects of early hippocampal pathology on episodic and semantic memory. - Vargha-Khadem, F; Gadian, D; Watkins, K; Connelly, A; Van Paesschen, W; Mishkin, M (1997)
Global anterograde amnesia is described in three patients with brain injuries that occurred in one case at birth, in another by age 4, and in the third at age 9. Magnetic resonance techniques revealed bilateral hippocampal pathology in all three cases. Remarkably, despite their pronounced amnesia for the episodes of everyday life, all three patients attended mainstream schools and attained levels of speech and language competence, literacy, and factual knowledge that are within the low average to average range. The findings provide support for the view that the episodic and semantic components of cognitive memory are partly dissociable, with only the episodic component being fully dependent on the hippocampus.